The Effect of Health on Economic Growth: A Production Function Approach for Turkey - Avcı, Halim Can; Çalışkan, Zafer (Panoeconomicus, 2024)
Until the Augmented Neo-Classical Growth Model developed by Mankiw, Romer and Weil, growth theories have ignored the human capital factor. This study aims to investigate the impact of health on economic growth in Turkey between 1960-2014 through a production function that includes human capital. Health and education are included in the production function as the two main components of human capital. The Multivariate Auto-Regressive Distributed Lag (ARDL) Bounds Test was conducted for empirical analysis. As a result, a significant long-term cointegration relationship was found between the variables. The results also indicate that a 1% increase in life expectancy at birth leads to a 0.67% increase in GDP, a 1% increase in the number of students per teacher in vocational and technical secondary education leads to a 0.21% decrease in GDP, and a 1% increase in the number of students per teacher in tertiary education leads to a 0.21% increase in GDP. Keywords: Economic growth, Health, ARDL bounds test, Production function, Turkey. JEL: C32, I10, I20, O40.